Professional Relationships Can Improve the Quality of Nursing Services at Wijaya Kusumah Kuningan Hospital, West Java, Indonesia - Aria Pranatha; Idris Adewale Ahmed; Nabillah G L (Journal of World Future Medicine, Health and Nursing, 2025)
Data from the Indonesian Ministry of Health (2020) shows that only 20% of health facilities measure service quality, with indicators such as patient identification compliance (66.67%) and emergency room response time (10.5%) still low. Professional relationship issues such as communication and collaboration between professionals also affect service quality, so that improvement efforts are needed to achieve quality services and are oriented towards patient satisfaction. The purpose of this study was to determine the relationship between professional relationships and the quality of nursing services. Methods: This study used a quantitative research method using a cross-sectional model. The population in this study were 58 nurses at Wijaya Kusumah Hospital, Kuningan, with a total sampling technique. The instruments used in this study were observation sheets and questionnaires. Data analysis was carried out according to univariate and bivariate using the Spearman Rank statistical test. Results: This study shows that most of the Professional Relationships were 47 people (81.0%), and of the 58 respondents, the quality of nursing services was mostly good (55 respondents (94.8%). The results of the Spearmen Rank test obtained a p value of 0.000 (<0.05) with an R value of 0.509. Conclusion: There is a significant relationship between Professional Relationship and the quality of nursing services in nursing services which include activities such as passes, nursing conferences, and nursing rounds, so that it can improve the nursing services provided to patients and strengthen the work team.